Assessing the Structural and Concurrent Validity of a Shortened Version of the Domestic Violence Healthcare Providers’ Survey Questionnaire for Use in Sweden - Lawoko, Stephen; Sanz, Sören; Helström, Lotti; Castren, Maaret (Psychology, 2012)
It has recently become incumbent on researchers to develop tools for the assessment of healthcare practitioners’ readiness to screen for Intimate Partner Violence (IPV). One such comprehensive tool is the Healthcare Provider Survey Scales (DVHPSS). Its usefulness in new settings however warrants a validity test. Aim: We assessed some aspects of the structural validity of a shortened version of the DVHPSS. Method: Health care workers at a health facility in Sweden (n = 193) responded to a shortened version of the DVHPSS. Exploratory factor analysis, Cronbach’s Alpha, correlation, T-test, and ANOVA were used to analyse the data. Criteria for inclusion were set a priori. Results: All items of the shortened DVHPSS were retained following analysis. A six factor model emerged, with slight modifications of the original scales. Concurrent validity of the emerging scales was confirmed. Conclusions: The DVHPSS is a valid tool to assess readiness to screen for IPV in Swedish healthcare
Keywords: Domestic Violence Survey; Structural Validity; Healthcare Providers; Sweden